Reactive RED 195 dye removal using chitosan coacervated particles as bio-sorbent: Analysis of kinetics, equilibrium and adsorption mechanisms - Perez Calderon, John Freddy (2018)
Chitosan particles (CP) prepared by coacervation technique were used as bio-sorbent material to remove the azo RR-195 dye; removal percentage (%RM) and adsorption capacity (Q) in batch adsorption experiments under different conditions of bio-sorbent doses, agitation speed and pH medium were determined; the maximum pH of dye removal was 4. Different adsorption equilibrium isotherms were tested and Redlich-Peterson was the model that best fitted experimental results. From the adsorption thermodynamic parameters, it was concluded that the adsorption process of RR-195 onto CP is spontaneous, favorable (ΔG<0), endothermic (ΔH>0) and the dye molecules show affinity for the bio-sorbent (ΔS>0). The maximum monolayer adsorption capacity (Qm) of CP was 82.1 mg.g-1 at pH = 4 and 318 K; therefore coacervated chitosan particles are among the top three adsorbent agents for this dye. The %RM was 84.2% in 10 h when the initial concentration of the dye was 300 mg.L-1. The mixed surface reaction and diffusion-controlled kinetic model (MSR-DCK), fitted satisfactorily experimental results, by considering simultaneous mechanisms of diffusion and adsorption process in the active sites. Fourier transform infrared spectroscopy (FTIR) with attenuated total reflection (ATR), scanning electron microscope-energy dispersion spectrometry X-ray (SEM-EDS) and Zeta potential analysis revealed that the interaction between dye molecules and the bio-sorbent are of an electrostatic nature. Desorption/regeneration experiments indicated that CP can be used in adsorptions/desorption cycles for the removal of wastewater containing RR-195. The information presented in this work demonstrates that CP can be a potent eco-friendly bio-adsorbent for the remediation of industrial wastewater.